Crystal structure of hemoglobin from the maned wolf (Chrysocyon brachyurus) using synchrotron radiation - Fadel, V; Canduri, F.; Olivieri, JR; Smarra, ALS; Colombo, M. F.; Bonilla-Rodriguez, G. O.; de Azevedo, W. F. (Bentham Science Publ Ltd, 2003)
Crystal structure of hemoglobin isolated from the Brazilian maned wolf (Chrysocyon brachyurus) was determined using standard molecular replacement technique and refined using maximum-likelihood and simulated annealing protocols to 1.87Angstrom resolution. Structural and functional comparisons between hemoglobins from the Chrysocyon brachyurus and Homo sapiens are discussed, in order to provide further insights in the comparative biochemistry of vertebrate hemoglobins.
Keywords: hemoglobin; synchrotron; Chrysocyon brachyurus; maned wolf